Improved Lipschitz bounds with the first norm for function values over multidimensional simplex - Paulavičius, Remigijus; Žilinskas, Julius (Mathematical Modelling and Analysis, 2008)
A branch and bound algorithm for global optimization is proposed, where the maximum of an upper bounding function based on Lipschitz condition and the first norm over a simplex is used as the upper bound of function. In this case the graph of bounding function is intersection of n‐dimensional pyramids and its maximum point is found solving a system of linear equations. The efficiency of the proposed global optimization algorithm is evaluated experimentally. First Published Online: 14 Oct 2010